Body Composition and respiratory parameters in different age groups of football players - Spirkoska Vangelovska, B; Nestorova, Mihaela; Dejanova, Beti; Ejupi A; Pluncevikj Gligoroska, Jasmina (Faculty of Physical Education, Sport and Health, Skopje, Republic of Macedonia, 2022)
Abstract Pulmonary function tests (PFTs) are commonly used for evaluating respiratory status in healthy subjects and for patients with pulmonary disease. They have also become a part of routine health examinations in respiratory, occupational, and sports medicine, and in public-health screening. The results of PFTs are interpreted in relation to normal range reference values, as recommended by the guidelines of the American Thoracic Society (ATS) and the European Community for Coal and Steel (ECCS). Spirometry is a gold standard of pulmonary function tests that measures the capacity of inhales and exhales volumes, more often as a function of time. It is often used in pulmonary function procedures, having become indispensable for the prevention, diagnosis, and evaluation of various respiratory impairments. A number of 61 football players were divided into 2 groups according to age: I group - below 18 years old (13.85 ± 3.26) and II group - above 18 years old (23.82 ± 3.32). This study was performed at the Institute of Medical, Experimental and Applied Physiology and Anthropology, Medical Faculty in Skopje. The spirometry method was performed with the Spirobank II spirometer (Rome, Italy), for the following parameters: forced vital capacity (FVC) in L, forced expiratory volume in the first second (FEV1) in L, and the ratio FEV1/FVC ratio (%). Body composition analyzer InBody 720, Great Britain, was used to determine body weight (kg), body height (cm), body mass index - BMI (kg/m2 ), skeletal muscle mass - SMM (kg) and the amount of proteins (kg) and minerals (kg). There was a significant difference in 2 examined groups of football players regarding all body composition parameters (p<0.001). No statistically significant difference was found for FVC, FEV1, and for the FEV1/FVC ratio. There was a difference in body composition parameters between the two age groups, without any influence on respiratory parameters. All these results may contribute to proper selection of training procedures, appropriate diet, and personalized performance. Key words: spirometry; pulmonary function; body composition.